2015
DOI: 10.1590/abd1806-4841.20153684
|View full text |Cite
|
Sign up to set email alerts
|

Translation, cross-cultural adaptation and validation of the vitiligo-specifi c health-related quality of life instrument (VitiQoL) into Brazilian Portuguese

Abstract: BACKGROUND:Vitiligo, although asymptomatic, highly compromises patients' quality of life (QoL). Therefore, an adequate evaluation of QoL is essential.OBJECTIVES:Translation, cultural adaptation and validation of VitiQol (Vitiligo-specific health-related quality of life instrument) into Brazilian Portuguese.METHODS:The study was conducted in two stages; the first stage was the translation and cultural/linguistic adaptation of the instrument; the second stage was the instrument's validation.RESULTS:The translate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
3
20
0
1
Order By: Relevance
“…As in previous studies with VitiQoL, there was a correlation between the VitiQoL and the DLQI and the individual patient's assessment of the severity of the disease [4,8] . Similarly, other specific questionnaires for vitiligo had shown a correlation with the DLQI [25,27,28] .…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…As in previous studies with VitiQoL, there was a correlation between the VitiQoL and the DLQI and the individual patient's assessment of the severity of the disease [4,8] . Similarly, other specific questionnaires for vitiligo had shown a correlation with the DLQI [25,27,28] .…”
Section: Discussionsupporting
confidence: 72%
“…We had already found a similar result when we validated the VitiQoL to Brazilian Portuguese [8] , because, in both studies, as well as in the original VitiQoL study [4] , the single item that most contributed to the total score was related to the frustration about the skin condition (question 2). This aspect is quite important, since it has already been observed that selfesteem of patients is greatly affected and that stigmatization is very present in the disease, as already assessed in previous studies [20,21] .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…1 This instrument has only been published in English, and we have been contacted by other health professionals to provide a validated version in Portuguese.…”
mentioning
confidence: 99%
“…After the English version publication of the vitiligo questionnaire, and once the Brazilian Portuguese version is published, the impact of vitiligo on the quality of life might be assessed by a specific instrument in Brazil. 1,2 Therefore, it will yield a more complete and reliable evaluation of patients both in medical offices and in new clinical trials.…”
mentioning
confidence: 99%